Active Proximal Sealing in the Endovascular Repair of Abdominal Aortic Aneurysms: Early Results With a New Stent-Graft. (April 2015) - Melas, Nikolaos; Stavridis, Kyriakos; Saratzis, Athanasios; Lazarides, John; Gitas, Christos; Saratzis, Nikolaos
Purpose: To investigate the performance of a new device that uses the STRATA polytetrafluoroethylene graft material and a mechanism that provides active proximal sealing in order to prevent type Ia endoleak during endovascular aneurysm repair (EVAR).Methods: Between April 2013 and July 2014, 21 consecutive patients (all men; median age 71 years, range 60–84 years) with abdominal aortic aneurysm (median diameter 5.9 cm, range 4.9–7.8 cm) and suitable anatomy were offered elective EVAR using the AFX endograft. These patients had an irregular, conical, tapered, or bulging proximal neck, for which this specific device was considered appropriate. Aneurysm exclusion and incidence of type Ia endoleak were the primary outcomes; secondary outcomes included mortality, morbidity, migration, and other graft-related complications.Results: Primary technical success was 90%; 2 intraoperative type Ia endoleaks due to low endograft deployment were treated with additional proximal cuffs. During a median follow-up of 10 months (range 2–15 months), no type I endoleak was observed. One type II endoleak was encountered, with no associated sac enlargement. There was no stent-graft migration or any other device-related complication. One patient had a nonfatal myocardial infarction and another developed renal failure requiring transient dialysis. No deaths occurred.Conclusion: In this early experience, this newly available device appears to be safe and efficient in providing seal along irregularly shaped necks over the short term.